Optimalisasi Strategi Pengembangan SDM Pendidikan Berbasis Kecerdasan Sosial sebagai Pilar Adaptabilitas Organisasi Pembelajaran di Era Disrupsi Digital - Ausat, Abu Muna Almaududi; Sutrisno; Pramono, Susatyo Adhi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine how social intelligence can be strategically integrated into educational HR development as a foundation for organizational adaptability. Using a qualitative approach with a literature review method and descriptive analysis, data were collected from 50 scholarly articles obtained via Google Scholar and various credible academic websites spanning the years 1990–2025, which were then rigorously filtered down to 31 core articles for analysis. Data analysis was conducted thematically by identifying patterns and key concepts from relevant literature to generate in-depth conclusions. The findings reveal that social intelligence plays a strategic role in enhancing collaboration, psychosocial resilience, and adaptive leadership within educational settings. Theories such as Multiple Intelligences, Emotional and Social Intelligence, and Learning Organization underpin the urgency of integrating social intelligence into HR strategies. Previous studies and practical cases support the assertion that social intelligence-based HR development has a tangible impact on the success of learning organization transformation in the digital era. This study recommends a reformulation of educational HR management policies by positioning social intelligence as a key measurable competence integrated into performance assessment systems, training programs, and the organizational culture of educational institutions.